2010
DOI: 10.1111/j.1399-3046.2010.01361.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric growth and utilization of enteral feeding support in pediatric heart transplant recipients

Abstract: We sought to outline trends in anthropometric growth before and after cardiac transplantation and to document our experience with the use of EFS in this population. A total of 130 patients (59% male) were enrolled and followed for a median of 4.4 yr after transplantation. Negative changes over time in weight z-score (EST: -0.256 [0.160] z/yr, p = 0.01), height z-score (EST: -0.214 [0.096] z/yr, p = 0.03), and BMI z-score (EST: -0.287 [0.161] z/yr, p = 0.07) were observed prior to transplantation. Significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 36 publications
(45 reference statements)
1
15
0
Order By: Relevance
“…According to Eurotransplant data 553, HTXs have been performed in total in 2009 inside the Eurotransplant countries . Malnutrition and its consequences for the long‐term survival and outcome after HTX are already recognized as major risk factors for pediatric as well as for adult patients . As patients after cardiac transplantation have to be administered more intensive immunosuppression as compared to patients after other solid organ transplantation, they are at higher risk for diseases triggered by immunosuppression as well .…”
Section: Discussionmentioning
confidence: 99%
“…According to Eurotransplant data 553, HTXs have been performed in total in 2009 inside the Eurotransplant countries . Malnutrition and its consequences for the long‐term survival and outcome after HTX are already recognized as major risk factors for pediatric as well as for adult patients . As patients after cardiac transplantation have to be administered more intensive immunosuppression as compared to patients after other solid organ transplantation, they are at higher risk for diseases triggered by immunosuppression as well .…”
Section: Discussionmentioning
confidence: 99%
“…Historically, with medical management of HF, nutritional rehabilitation has been difficult to achieve in children awaiting HT, even when enteral feeds, caloric supplementation, or TPN are used . Studies have shown that malnutrition occurs commonly in children listed for HT and often worsens through the waitlist period .…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that 17% of the population became overweight by 2 years posttransplant and noted that increases in weight without corresponding height may result in obesity. In a more recent study of 130 pediatric heart transplant recipients, Bannister et al 39 reported that enteral feeding support during the posttransplant period significantly improved rates of weight and height gain. However, anthropometric measures did not reach normal values during the study follow‐up period (median 4.4 years after transplantation).…”
Section: Nutrition Goalsmentioning
confidence: 99%
“…Children with coronary heart disease or cardiomyopathy with end‐stage heart failure are at risk for failure to thrive due to multiple hospitalizations for surgical procedures, 39 feeding intolerance and malabsorption, 60 and possibly increased energy requirements 61 . The effect of undernutrition on adverse outcomes is unclear.…”
Section: Case Presentationsmentioning
confidence: 99%
See 1 more Smart Citation